Russel - Silver syndrome a 7-month-old child: case report - N.R. Khafizova; D.R. Merzlyakova; Yu.F. Safina (LCC «Medicine-Inform», 2021)
N.R. Khafizova, D.R. Merzlyakova, Yu.F. Safina Bashkir State Medical University, Ufa, Russian Federation Russel - Silver syndrome (RSS) is a hereditary disease manifesting with intrauterine growth retardation, dwarfism, and other stigmas of embryopathy. We describe this rare genetic condition in a 7-month-old baby. The changes in physical condition and neurological status, clinical signs, laboratory tests, and management strategy are addressed. A genetic condition was suggested through an arrested development and stigmas of embryopathy only at the age of 7 months. At the age of 5 months, hydrocephaly was suspected due to asymmetrical proportions of the body (the relatively large size of head compared to a small body). However, neurosonography ruled out this diagnosis. Genetic testing for microsatellite loci on chromosome 7, which identified abnormal methylation of H19 gene verified the final diagnosis. Keywords: Russel - Silver syndrome, child, intrauterine growth retardation, pseudohydrocephalus, dwarfism, genetic counseling. For citation: Khafizova N.R., Merzlyakova D.R., Safina Yu.F. Russel - Silver syndrome a 7-month-old child: case report. Russian Journal of Woman and Child Health. 2021;4(1):103-105. DOI: 10.32364/2618-8430-2021-4-1-103-105.